FUNDAMENTALS OF RADIO CONTROL OF FAULTY EQUIPMENT AND ICE REGIMES ARC ABUSES OF POWER COLLECTION - Zharkov, Yu. I.; Semenov, Yu. H. (Science and Transport Progress, 2009)
The principles of construction and the structure of radio system for detecting damaged current collectors and glaze-ice regimes on arc breaking of current collection as well as the peculiarities of received radio signals and the basics of their identification are presented.